2010
DOI: 10.1088/1674-4527/10/10/002
|View full text |Cite
|
Sign up to set email alerts
|

Does a low solar cycle minimum hint at a weak upcoming cycle?

Abstract: The maximum amplitude (R m ) of a solar cycle, in the term of mean sunspot numbers, is well-known to be positively correlated with the preceding minimum (R min ). So far as the long term trend is concerned, a low level of R min tends to be followed by a weak R m , and vice versa. In this paper, we found that the evidence is insufficient to infer a very weak Cycle 24 from the very low R min in the preceding cycle. This is concluded by analyzing the correlation in the temporal variations of parameters for two su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…The amplitudes of solar cycle 24 predicted by researcher are quite dispersed (Obridko and Shelting 2008;Pesnell 2008;Bhatt et al 2009;Ajabshirizadeh 2011;Chumak and Matveychuk 2010;Dabas and Sharma 2010;Du and Wang 2010;Kane 2010;Wang et al, 2002Wang et al, , 2008Wang et al, , 2009). However, a dynamo model tends to predict that the amplitude of solar cycle 24 is about 90 or even at less than 90 (Jiang et al 2007).…”
Section: Summary and Discussionmentioning
confidence: 90%
“…The amplitudes of solar cycle 24 predicted by researcher are quite dispersed (Obridko and Shelting 2008;Pesnell 2008;Bhatt et al 2009;Ajabshirizadeh 2011;Chumak and Matveychuk 2010;Dabas and Sharma 2010;Du and Wang 2010;Kane 2010;Wang et al, 2002Wang et al, , 2008Wang et al, , 2009). However, a dynamo model tends to predict that the amplitude of solar cycle 24 is about 90 or even at less than 90 (Jiang et al 2007).…”
Section: Summary and Discussionmentioning
confidence: 90%
“…For example, Ohl's geomagnetic precursor method [18] succeeded in predicting R max in cycles 20-22 [19][20][21][22] due to the high correlation coefficients (> 0.8) between R max and geomagnetic-based parameters. However, a high correlation does not always yield a satisfactory prediction [5][6][7][23][24][25] and a low correlation may also yield an accurate prediction in some cases (see sect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a high correlation is not the sole condition to obtain a more accurate prediction [23][24][25][26][27], which may depend on the variation of the correlation or long-term periodicities [5][6][7][24][25]. In this study, R max can be well estimated from β a even if the correlation coefficient (r) is not strong near the initial phase in some cycles, e.g., E < 20% for small r (< 0.5) at small Δm in cycles 15, 20, 22 and 23 (see Figure 2).…”
Section: 2)mentioning
confidence: 99%
“…Curve (continuous line) depicting the running correlation, r(5,n), of R max and R min evaluated with a moving time window of 5 cycles is shown in the bottom panel of Figure 4. It is quite apparent that the correlations become negative beyond Cycle 18 (Du and Wang, 2010). However the correlations beyond Cycle 18 also become positive (dotted line between Cycles 16 and 21 shown in the bottom panel) when Cycle 19 is eliminated from the analysis.…”
Section: Trends In Recent Cyclesmentioning
confidence: 95%
“…Through an analysis of trends, V m [sign{R max (i) -R max (i-1)}] and V min [sign {R min (i) -R min (i-1)}] Du and Wang (2010) have supported the view that the R max versus R min relation is not always effective for individual cycles (Wang and Sheeley, 2009) and that the negative correlation between V m and V min cannot account for the predicted (Pesnell, 2008 and references therein) very weak R max for the very low R min . Based on the analysis of temporal variation in the running correlations they have indicated that a lower R min has not always been followed by a weaker R max and therefore inferred that Cycle 24 need not be a very weak cycle.…”
Section: Trends Of Variation In Consecutive Cyclesmentioning
confidence: 99%